The Role of Antioxidant Therapy in the Management of Type 2 Diabetes Mellitus: A Literature Review - Astini, Dewa Ayu Agung Alit Suka; Yasa, I Wayan Putu Sutirta; Jawi, I Made; Wande, I Nyoman (Faculty of Medicine, Public Health, and Nursing, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disease and has become a global problem due to the rapid increase in the number of cases. This disease is characterized by chronic hyperglycemia caused by insulin resistance and pancreatic beta cell dysfunction. The occurrence of oxidative stress is known to play a central role in the development of T2DM complications, through increased reactive oxygen species (ROS) that worsen insulin resistance, worsen beta cell function, and trigger complications such as cardiovascular complications, nephropathy, and neuropathy. Objectives: This literature review aims to evaluate the scientific evidence supporting the use of antioxidant therapy as an additional approach in the management of T2DM, focusing on the effectiveness and mechanism of action of antioxidant compounds on glycemic parameters, oxidative stress, and diabetes complications. Methods: A literature search was conducted through databases on ScienceDirect, PubMed, and Google Scholar, with the keywords